Can a validated website help improve university students’ e-health literacy? - Conte, A.; Brunelli, L.; Moretti, V.; Valdi, G.; Guelfi, M. R.; Masoni, M.; Anelli, F.; Parpinel, M.; Arnoldo, L. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The fight against fake news, mainly spread through Internet, is a major public health issue, even among undergraduate students. This study aims to evaluate the effectiveness of a website promoted by the Italian Federation of the Provincial Orders of the Medical Doctors as a first aid communication kit for health topics. Study design. Pre-post study using a web-based survey, conducted in April-May 2019 on Medical students and October-November 2020 on Communication Sciences students at the University of Florence (Italy). Methods. Undergraduate students of both schools were exposed to the use of the “dottoremaeveroche” website. Primary and secondary outcomes measures: the Italian-electronic Health Literacy Scale self-assessment tool was used to examine subjects’ electronic Health literacy, and source quality. All responses were rated on a 5-point Likert scale. Changing in perception of abilities were examined using the Wilcoxon test. Results. The 362 participants felt moderately confident in electronic Health Literacy, with an initial Italian-electronic Health Literacy Scale overall mean score of 3.6±0.7 for medical and 3.2±0.8 for communication students. Medical students had a good idea of how to find helpful sources (3.9±0.8) and communication students felt confident in recognizing their quality (3.5±1.0). In contrast, their confidence in using Web information to make health decisions was low (medical: 2.9±1.1; communication: 2.8±1.1). All items improved significantly after “dottoremaeveroche” use (p<.001), with the overall mean score of Italian-electronic Health Literacy Scale increasing to 4.3±0.6 for medical and 4.1±0.8 for communication students. Conclusions. Low electronic health literacy levels can affect public health efforts, as seen during the COVID19 pandemic. The effectiveness of “dottoremaeveroche” among students showed the usefulness of online educational interventions that, if further implemented, could help combat the spread of infodemic.